Mechanisms of obesity in Prader–Willi syndrome. Issue 1 (10th November 2016) - Khan, M. J.; Gerasimidis, K.; Edwards, C. A.; Shaikh, M. G.
Summary: Obesity is the most common cause of metabolic complications and poor quality of life in Prader–Willi syndrome (PWS). Hyperphagia and obesity develop after an initial phase of poor feeding and failure to thrive. Several mechanisms for the aetiology of obesity in PWS are proposed, which include disruption in hypothalamic pathways of satiety control resulting in hyperphagia, aberration in hormones regulating food intake, reduced energy expenditure because of hypotonia and altered behaviour with features of autism spectrum disorder. Profound muscular hypotonia prevents PWS patients from becoming physically active, causing reduced muscle movements and hence reduced energy expenditure. In a quest for the aetiology of obesity, recent evidence has focused on several appetite‐regulating hormones, growth hormone, thyroid hormones and plasma adipocytokines. However, despite advancement in understanding of the genetic basis of PWS, there are contradictory data on the role of satiety hormones in hyperphagia and data regarding dietary intake are limited. Mechanistic studies on the aetiology of obesity and its relationship with disease pathogenesis in PWS are required. . In this review, we focused on the available evidence regarding mechanisms of obesity and potential new areas that could be explored to help unravel obesity pathogenesis in PWS.